O diálogo como resposta à judicialização da saúde no município de Barreiras – BA - Calixto, Fabiana de Carvalho (2022)
This research approaches the issue of Philosophical Education in prison. The central aim is to raise reflections within the prisoners about the founding causes for their own incarcerations. Furthermore, about the necessity to search for knowledge to illustrate one’s actions in order to avoid criminal recidivism which causes a new incarceration upon completion of sentence. The course of this investigation and philosophical practice addresses three diachronic periods of time. Firstly, with the assistance of Michel Foucault, this study approaches the basis and definition of the misconceptions in prison while recognizing the disassociation which occurs from the serving of the sentences to their learning purposes. Secondly, assisted by Plato, through his dialectic and The Allegory of the Cave, the discernment and identification together with the incarcerated population of the true shadows present inside the regulations of the crime world. From there, the perspective of one’s ability to avoid attitudes based on opinions, pre-judgement and prejudice, such as, chauvinist attitudes towards women, the practical target of this intervention, which caused the incarceration and may cause recidivism. Thirdly, the construction of a philosophical practice, based on the platonic maieutic and contemplated by traumatisms and groping, that lead the prisoners to the affection of their own existence. Accordingly, this aims to provide for the possibility to remission and transcendency of one’s crimes from the humane movement of one’s interiorities. This is the significant result to be achieved by this investigation and practice of Philosophy Education as means towards comprehension of the liberty within imprisonment, from The Allegory of the Cave – Prison Nevermore.